2018
DOI: 10.1002/adsc.201701345
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Azidation of α‐Hydroxy Esters and α‐Hydroxy Ketones Using Azidotrimethylsilane

Abstract: We herein report a commercially available perchloric acid catalyst capable of catalyzing the azidation of a-hydroxy esters, a-hydroxy ketones and taddols using azidotrimethylsilane in dichloromethane at room temperature. Various substituted tertiary alcohols are well tolerated in this reaction. C a -tetrasubstituted a-amino acid derivatives were prepared by one-pot sequential azidation and hydrogenation procedure. The advantage of this newly developed method includes operational simplicity, ready availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In particular, exploitation of azides in the Huisgen reaction or in Click chemistry provides crucial methods for coupling between biomarkers and macromolecules 11 . However, in most synthetic protocols for azido compounds, free alcohols are employed as substrates 12 . Therefore, the scope of the AlCl 3 ‐catalyzed protocol was extended to direct azidation from MOM‐protected alcohols, as illustrated in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, exploitation of azides in the Huisgen reaction or in Click chemistry provides crucial methods for coupling between biomarkers and macromolecules 11 . However, in most synthetic protocols for azido compounds, free alcohols are employed as substrates 12 . Therefore, the scope of the AlCl 3 ‐catalyzed protocol was extended to direct azidation from MOM‐protected alcohols, as illustrated in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Rode accomplished it with the use of a solid povidone and phosphotungstic acid hybrid as a catalyst for heterogeneous azidation of alcohols . More recently, Zhou and Regier achieved it with aqueous perchloric acid and HBF 4 ·OEt 2, respectively (Figure ). Although numerous methods for azidation exist, a more convenient method for the safer generation of azide is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction provides the most straightforward access to the α-hydroxy-β-dicarbonyl, an intriguing moiety commonly found in various biologically active natural products, agrochemicals, and pharmaceuticals [25][26][27]. Notably, a number of chemical protocols are available to accomplish this oxidation to yield product 2 [28][29][30][31][32][33]. For instance, Lu et al reported a Brønsted acid catalytic method with nitrosobenzene as the oxygen source [28], and Meng and co-workers documented a Zr(IV)/organic peroxide system [30].…”
Section: Introductionmentioning
confidence: 99%